A Study on Shariah Issues of Tabarru’ and Underwriting Surplus in Takaful - Devi, Abrista (SMART Insight, 2023)
Surplus underwriting in the context of Islamic insurance (takaful) refers to the process of managing and distributing any surplus that may arise in the takaful fund after covering claims and operational expenses. This paper attempts to discuss two sharia issue regarding the tabarru’ concept that is applied in takaful operations, and underwriting surplus of the tabarru’ fund. To obtain coherent and comprehensive analysis, this paper discusses the opinion from the opponents and the proponent’s side of view. There are two main views, whereby AAOIFI, IFSB, and Fatawa Ta’min, Dallah al-Barakah stated that underwriting surplus must be fully distributed to the participants. Meanwhile, SAC-BNM, MUI (Majelis Ulama Indonesia), and the majority of scholars are of the view that underwriting surplus is allowed to be shared between participant’s and takaful institution as long as stipulated upfront in the contract.